Microleakage of glass ionomer cement restorations - Davidović Lado; Tomić Slavoljub; Stanojević Mihael; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. A lack of appropriate adhesiveness is one of the biggest problems in the restorative dentistry today and the main cause of the microleakage between restorations and hard dental tissue. The aim of this study was to assess the adhesiveness of two different glass ionomer cement restorations class V on the hard dental tissue using the SEM analysis and dye penetration test. Material and methods. The study included 80 extracted teeth for orthodontic reasons (premolars and molars) in both genders and different age. On the vestibular and oral side of the teeth, adhesive preparations class V were done (size 3Ч2Ч2 mm). On the vestibular preparation, GC Fuji II was applicated and GC Fuji II LC-improved on the oral side. The quality of the adhesiveness between restorations and hard dental tissue was evaluated using the SEM analysis and dye penetration test (0.5% basic fuxsin). Linear penetration of the dye was observed using 10 times magnification. Results. The results showed that microleakage was presented with both materials but a ratio was less with Fuji II LC compared with Fuji II. Also, the microleakage was less on the occlusal parts of the restorations than on the gingival, with both materials. Microleakage was noticed in 93.44% teeth with Fuji II GJC restorations with index of microleakage of 148 on all edges. Fuji II LC GJC restorations showed microleakage in 68.4% teeth with index of microleakage 75 on all edges. The SEM analysis showed that both glass ionomer materials had better adhesiveness to the enamel than to the dentin. The average gap length between Fuji II LC and dentin was 9 μm and Fuji II 17 μm, respectively. Conclusion. Better adhesiveness to the hard dental tissue was achieved with materials of the newer generations, resin modificated glas ionomer cements.